Presurgical nasoalveolar molding orthopedic treatment improves the outcome of primary cheiloplasty of unilateral complete cleft lip and palate, as assessed by naris morphology and cleft gap - Sasaki, Hiroyoshi; Togashi, Shinji; Karube, Rei; Yanagawa, Toru; Nakane, Shizuo; Tabuchi, Katsuhiko; Ishibashi, Naomi; Shinya, Yoshiko; Ito, Hiroyuki; Yamagata, Kenji; Onizawa, Kojiro; Adachi, Koji; et al. (The Journal of craniofacial surgery, 2012)
We evaluated the effects of presurgical nasoalveolar molding (NAM) with an orthopedic appliance and compared them with a passive orthopedic method (Hotz plate, HP), focusing on the naris morphology and width of the alveolar and palate cleft gap. The subjects were 28 unilateral complete cleft lip and palate patients treated with primary cheiloplasty at Tsukuba University Hospital from 2004 to 2011. Thirteen patients were treated preoperatively with NAM (NAM group), and 15 with HP (HP group). The surgical outcome was assessed according to left-right naris symmetry, as measured by the area ratio, perimeter ratio, aspect a/u ratio (aspect ratio of the affected side/aspect ratio of the unaffected side), and Hausdorff distance. In addition, the alveolar and palate cleft width was measured at the times of orthopedic plate setting and primary cheiloplasty. The aspect ratio was significantly smaller in the NAM group than in the HP group before the operation. In both groups, the aspect ratio, perimeter ratio, and Hausdorff distance were significantly smaller after the operation than before. The width of the alveolar and palate cleft gap was significantly narrowed in the NAM group, and the cleft gap at the initiation of NAM correlated significantly with the Hausdorff distance after cheiloplasty. We found that NAM improved the form of the naris after primary cheiloplasty and decreased the palate cleft gap more effectively than HP and that the width of the palate cleft gap was correlated with the surgical outcome of the naris.